UJI DAYA TERIMA MI YANG DISUBSTITUSI DENGAN AMPAS TAHU DAN BIT (Beta vulgaris) - Rahmawati Wardani; Zulhaida Lubis; Fitri Ardiani (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2017)
Communities in Indonesia consume noodles as an alternative food for rice. Noodles is a type of food made from wheat flour. Wheat flour is an imported commodity. Therefore, it is necessary to develop technique for production of noodles which are mannering to reducing take of wheat flour, for example by making use of tofu waste. Tofu waste is a byproduct of soybean processing to tofu. Based on its nutrient content,tofu waste are potential as a source of nutrition, which contains proteins and fiber. Beetroot used to as  a natural dye for food which contains antioxidant and calium. The purpose of this research was to know acceptance of wet noodle including color, flavor, taste, and texture which is tested through a hedonic test. This research was an experimental research with 2 treatments of tofu waste substitutions, which was 20% and 30% of total dough weight and beetroot 10% for each treatment. Panelist in this research was 30 students of Public Health Faculty in Sumatera Utara University. Acceptance data test was analyzed with Wilcoxon Signed-Ranks. Nutrient wasanalyzedin Laboratory of Industrial Research and Standardization Agency Medan. The substitution of tofu waste and beetroot with different concentrations in making of wet noodles give a different effect on the color and flavor, but don’t give a different effect on the taste and texture of wet noodles. The characterization of wet noodle showed increasing nutrient with addition tofu waste. The experiment showed that wet noodle with the substitution of tofu waste-beetroot 20% : 10% was prefered by color and 30% : 10% was prefered by flavor, taste, and texture. It is suggestionedfor consumer to make wet noodles with substitusion of tofu waste and beetroot  as an alternative food for rice. Keywords: AcceptanceTest, Wet Noodles, Tofu Waste, Beetroot